2016
DOI: 10.1152/ajpendo.00496.2015
|View full text |Cite
|
Sign up to set email alerts
|

The incretin effect in obese adolescents with and without type 2 diabetes: impaired or intact?

Abstract: The incretin effect reflects the actions of enteral stimuli to promote prandial insulin secretion. Impairment of this measure has been proposed as an early marker of β-cell dysfunction and described in T2D, IGT, and even obesity without IGT. We sought to determine the effects of obesity and diabetes on the incretin effect in young subjects with short exposures to metabolic abnormalities and a few other confounding medical conditions. Subjects with T2D (n = 10; 18.0 ± 0.4 yr) or NGT, either obese (n = 11; 17.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 45 publications
(74 reference statements)
1
31
2
Order By: Relevance
“…Lesser degree of reduction in incretin effect has also been observed in two other studies among non-Asian youth with T2DM. 10 37 However, the incretin effect was derived differently from all three studies making direct comparison inaccurate. The greater reduction in incretin effect in our study may be due to the poorer glycemic control among our subjects since hyperglycemia has been proposed to downregulate GLP-1 receptor expression on β-cells and cause ‘GLP-1 resistance’.…”
Section: Discussionmentioning
confidence: 99%
“…Lesser degree of reduction in incretin effect has also been observed in two other studies among non-Asian youth with T2DM. 10 37 However, the incretin effect was derived differently from all three studies making direct comparison inaccurate. The greater reduction in incretin effect in our study may be due to the poorer glycemic control among our subjects since hyperglycemia has been proposed to downregulate GLP-1 receptor expression on β-cells and cause ‘GLP-1 resistance’.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes in adults is associated with a diminished incretin effect, reflecting reductions in the insulinotropic response to GIP, functioning beta cell mass and maximum insulin secretory capacity . Despite variation in the reported concentrations of GIP and GLP‐1 (both reduced and increased), meta‐analyses indicate that there is no substantial alteration in GIP or GLP‐1 secretion in type 2 diabetes . A reduced incretin effect is also seen in adolescents with impaired glucose tolerance or type 2 diabetes .…”
Section: What Enteroendocrine Factors Influence Postprandial Glycaemia?mentioning
confidence: 99%
“…Despite variation in the reported concentrations of GIP and GLP‐1 (both reduced and increased), meta‐analyses indicate that there is no substantial alteration in GIP or GLP‐1 secretion in type 2 diabetes . A reduced incretin effect is also seen in adolescents with impaired glucose tolerance or type 2 diabetes . In type 1 diabetes, there is, predictability, a reduced incretin effect in terms of insulin response, and glucagon suppression is also impaired …”
Section: What Enteroendocrine Factors Influence Postprandial Glycaemia?mentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 Numerous researches have reported that the function of incretin axis is impaired in T2D or metabolic syndrome, a phenomenon that causes insufficient GLP-1 production, or disrupted GLP-1 action. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%